In search of the “secret manual” in the Chinese “wuxia” world: re-examining the ethos of “wuxia” film “Crouching Tiger, Hidden Dragon - Sijie, Mao; Wei, Chow Ow; Chiat, Loo Fung; Yasin, Megat Al Imran (LLC Scientific Industrial Enterprise "Genesis. Frontier. Science", 2025)
Wuxia, a standardised epic genre originating from a typical Chinese literature, has inspired mainstream global films for almost a century of motion picture evolution. Nevertheless, it often appears distant and enigmatic to certain audience, largely because of being set in an imagined ancient Chinese world underpinned by chivalrous and righteous ideals. It is therefore a challenge for filmmakers to strategically visualise the wuxia realm and materialise the jianghu world into a convincingly authentic depiction of in ancient China. Building on Aristotle’s concept of ethos, this study constructs a conceptual framework grounded in wu, xia, and jianghu, treating film as a deliberately orchestrated form of rhetoric. Through a microanalysis on the audiovisual elements with a special focus in “Crouching Tiger, Hidden Dragon” (2000), this research aims to uncover the “secret manual” behind wuxia film through an illumination of strategic filmmaking methods in the ethos established from the Chinese martial arts world. The findings offer a paradigmatic approach for wuxia filmmaking: one that not only harnesses audiovisual elements to fulfil narrative function but also integrates them with Chinese aesthetics and cultural traditions. By clarifying the complex interplay of audiovisual elements, this research enhances the understanding of the cultural and rhetorical factors that shape contemporary Chinese audience. Furthermore, by integrating classical rhetorical theory with modern film analysis, the study provides a robust framework for examining the enduring influence of wuxia storytelling through the cinematic landscape as presented in a significant wuxia film of the era.